2018
DOI: 10.1128/aac.02128-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Transfer and Microevolution of Avian Native IncA/C 2 bla NDM-1 -Carrying Plasmid pRH-1238 during a Broiler Chicken Infection Study

Abstract: The emergence and spread of carbapenemase-producing Enterobacteriaceae (CPE) in wildlife and livestock animals pose an important safety concern for public health. With our in vivo broiler chicken infection study, we investigated the transfer and experimental microevolution of the blaNDM-1-carrying IncA/C2 plasmid (pRH-1238) introduced by avian native Salmonella enterica subsp. enterica serovar Corvallis without inducing antibiotic selection pressure. We evaluated the dependency of the time point of inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…The pSE12-01738-2 plasmid is a derivative of the bla NDM-1 -carrying IncA/C 2 multiresistance plasmid pRH-1238 (GenBank accession number KR091911), previously described by Villa et al (7) but lacking a genetic element including genes for chromate and macrolide resistance as well as a class I integron carrying dfrA7-aadA5-sul1 resistance gene cassettes. This, along with previously observed structural deletions in pRH-1238 after an in vivo passage, indicates certain evolutionary plasticity, still enabling maintenance of the bla NDM-1 gene (8). …”
Section: Genome Announcementsupporting
confidence: 71%
See 1 more Smart Citation
“…The pSE12-01738-2 plasmid is a derivative of the bla NDM-1 -carrying IncA/C 2 multiresistance plasmid pRH-1238 (GenBank accession number KR091911), previously described by Villa et al (7) but lacking a genetic element including genes for chromate and macrolide resistance as well as a class I integron carrying dfrA7-aadA5-sul1 resistance gene cassettes. This, along with previously observed structural deletions in pRH-1238 after an in vivo passage, indicates certain evolutionary plasticity, still enabling maintenance of the bla NDM-1 gene (8). …”
Section: Genome Announcementsupporting
confidence: 71%
“…In recent in vivo infection studies, we demonstrated the persistence of this strain in broiler chickens and dissemination of its IncA/C 2 bla NDM-1 -carrying plasmid to different Enterobacteriaceae , both without antibiotic pressure (8). Such observations are noteworthy due to a possible scenario of bla NDM-1 introduction into commercial broiler production and downstream in the production chain, posing a subsequent risk for human exposure.…”
Section: Genome Announcementmentioning
confidence: 95%
“…plasmid within different enterobacterial species was recently reported in infected chickens, but also in hospitalized patients, with a single IncC plasmid (published as IncA/C 2 ) being identified in Citrobacter freundii, E. coli, K. pneumoniae and Klebsiella oxytoca. 16,17 NDM-1-producing P. mirabilis have been previously reported in different parts of the world, but usually the bla NDM-1 gene was identified within an SGI-type genomic island, hence at a chromosomal location. 18 Here, we showed it may also be found as plasmid located, on a broad host range IncC plasmid co-encoding b-lactamases CMY and TEM, in addition to the 16S rRNA methylase ArmA, as previously found.…”
Section: Resultsmentioning
confidence: 99%
“…Selected mcr-5carrying strains were used as a donor for filter mating conjugation studies using sodium azide-resistant E. coli K-12 J53 recipient cells. Filter mating conjugation was performed as previously described (33). The reaction mixtures were plated on transconjugant selective plates containing 1 mg/liter colistin sulfate and 100 mg/liter sodium azide (Sigma-Aldrich, Darmstadt, Germany) and incubated for approximately 42 h at 37°C.…”
Section: Characterization Of Mcr-5-harboring Salmonella Strainsmentioning
confidence: 99%